First record of the Chinese fanray, Platyrhina sinensis (Elasmobranchii: Myliobatiformes: Platyrhinidae), in the seawaters of Zhujiajian, Zhoushan, China - Z. Chen; X. Wang; J. Zhang; Y. Li; T. Gao; L. Lin (Acta Ichthyologica et Piscatoria, 2018)
There are several studies of the ichthyofauna of the East China Sea, however, the knowledge of fishes from this region still remains incomplete. This report confirms the occurrence of Chinese fanray, Platyrhina sinensis (Bloch et Schneider, 1801), in the seawaters of Zhoushan by analysing nine specimens of the Chinese fanray obtained in Zhujiajian from May 2017 to December 2017. The morphometric measurements and meristic counts were taken. The principal characters that are conclusive for the species were consistent with P. sinensis and were sufficient for separation of the examined specimens from other Platyrhina species. In addition, the fragment of 12S rRNA was also sequenced for the purpose of classification. The mean genetic distance within P. sinensis group was 0.71%, group mean distance between P. sinensis and other Platyrhina species ranged from 6.01% to 7.71%. Species were also separated from each other at the genetic level. Given the Chinese fanray has not been reported to exist in this region, our findings represent the first record from Zhoushan and extend the distribution range of this species into the north of the East China Sea. The reason behind the observed northward migration of some P. sinensis individuals from their southern habitat might be global warming. Collection of many additional specimens is needed to better define the geographic limits of the Chinese fanray.